ANALISIS KONDISI LAMUN (SEAGRASS) DI PERAIRAN PULAU PRAMUKA, KEPULAUAN SERIBU - Septi Dwi Fajarwati; Asma Irma Setianingsih; Muzani Muzani (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2015)
ABSTRACT This research aims to analyze the condition of seagrass ecosystem to see water quality data of the seagrass habitat and percentage cover of seagrass in the waters of the Pramuka Island, Seribu Islands. The research was conducted over two months from October to November 2014.This research used a descriptive method with field survey approach. The population in this study is the seagrass in Waters Pramuka Island. Determining the location with purposive sampling of the sampling is divided into three stations is North, East and South. Data collection techniques include primary data and secondary data. Primary data is data of seagrass (type, percentage cover and density of seagrass) and data of seagrass habitat environmental parameters (water temperature, current speed, brightness, depth, salinity, substrate, TSS, DO, pH) were obtained by direct measurement in the field, while secondary data include the general state of the research sites. Data analysis techniques used in this study using analysis of community structure of seagrass and water quality analysis. The results showed that seagrass species found in the Pramuka Island there are 6 types of seagrass Cymodocea rotundata, Cymodocea serrulata, Enhalus acoroides, Halophila ovalis, Halodule uninervis, Thalassia hemprichii. Conditions of seagrass in the waters of the Pramuka Island included into the category of less healthy-poor seagrass. At station 1 percentage by 31% classified seagrass less healthy conditions, while the other two stations are stations 2 and 3 belong to the category of the poor condition of seagrass, with each percentage cover of seagrass 19.4% and 20.3%. Of all water quality parameters measured, all the parameters are still in normal circumstances, but there are some parameters whose value is high at some stations TSS and pH value is high at station 2 with a value of TSS 18 mg/l and a pH value of 8.2. Water quality and seagrass communities in station 1 is still in good condition for the growth of seagrass, because at this station is an unspoiled area away from human activity, while the stations 2 and 3 have undergone changes in community structure of seagrass because at this station has several anthropogenic activities that disrupt the lives of seagrass, mostly from human activities such as domestic sewage and hoarding/reclamation, which affects the condition of seagrass at station 2 and 3 are poor seagrass. Keyword: Seagrass, Water Quality, Pramuka Island